Castellated structures behaviour under QSPA Kh-50 plasma exposures in ITER relevant conditions - Herashchenko, S.S.; Makhlaj, V.A.; Aksenov, N.N.; Bazylev, B.; Byrka, O.V.; Chebotarev, V.V.; Kulik, N.V.; Lebedev, S.I.; Shevchuk, P.B.; Staltsov, V.V. (Вопросы атомной науки и техники, 2014)
The experimental study of castellated target erosion under relevant to ITER ELMs surface heat load (i.e., energy density and the pulse duration as well as particle loads) was performed in QSPA Kh-50 quasi-stationary plasma accelerator. The damage of surface, mechanisms of solid/liquid particle ejection for different parts of castellated targets exposed to QSPA plasma streams has been studied in the course of increasing number of pulses. It is shown that melt dynamics at the structure edges, droplet splashing and molten bridges through the slits are determining processes in macroscopic erosion of castellated surface structures. На квазистационарном плазменном ускорителе КСПУ Х-50 проведено экспериментальное изучение эрозии зубчатых мишеней под воздействием поверхностных тепловых (удельная энергия и длительность импульса) и корпускулярных нагрузок, характерных для режимов ELM в ИТЭР. Повреждение поверхности, механизмы эжекции частиц в твердой и капельной фазе из различных частей мишени исследованы в зависимости от количества плазменных импульсов. Показано, что динамика движения расплава на границах структур, разбрызгивание капель и появление «мостиков» расплава через зазоры между составляющими мишени являются определяющими процессами в макроскопической эрозии составных поверхностных структур. На квазістаціонарному плазмовому прискорювачі КСПП Х-50 проведено експериментальне вивчення ерозії зубчастих мішеней під впливом поверхневих теплових (питома енергія і тривалість імпульсу) і корпускулярних навантажень, характерних для режимів ELM в ІТЕР. Пошкодження поверхні, механізми ежекції частинок в твердій і крапельній фазі з різних частин мішені досліджені в залежності від кількості плазмових імпульсів. Показано, що динаміка руху розплаву на межах структур, розбризкування крапель і поява «містків» розплаву через зазори між складовими мішені є визначальними процесами в макроскопічній ерозії складених поверхневих структур.